مقولات النّحو الوظيفي العربي في سورة الشّرح - نجاة, طواهر (جامعة الوادي - University of Eloued, 2022)
ملخص: اللغة ظاهرة اجتماعية متوارية في أذهان مستعمليها ، تحكمها أنظمة ووظائف تحدّد بناءها ، لذا فدراستها لا تقف عند نظرية صورية أو وظيفيّة ، وقد تجاوز اللسانيون في توصيفها البنية إلى الوظيفة وصولا إلى موضعها في الدّماغ رصدا لآلياتها ذهنيّا ، ويمثّل القرآن الكريم منذ نزوله نواة البحث اللغوي فلم يبق حبيس النحو والبلاغة ، بل تداركتهما علوم شتى ، لعل أجددها اللسانيات ، لأنّ النّص الشرعي إذا ما تناولناه لسانيّا وجدنا له أطرا تواصليّة ، تواصليّة توجّهها خصائص وسمات مباشرة وغير مباشرة إلى مخاطب صريح أو مضمر ، خطاب له قضايا،و أبعاد تداولية دلالية تظهر في تحقّقات صوتية ، أغراضه متعدّدة. Abstract: Quotations of Arabic Functional Grammar: Case Study of Surat “Al-Sharh”. Language is a social phenomenon hidden in the minds of its users and governed by systems and functions that determine its structure. Accordingly, its study is not restricted to formal or functional theories locked into grammar and rhetoric only. Linguists then extended the language description from its structure to its function to finally reach its position in the brain so as to detect its mechanisms mentally. Since its inception, the holly Qur’an has represented the nucleus of linguistic research. Hence, it has not been kept locked up in grammar and rhetoric, but it was rather approached by other various sciences such as linguistics which is considered the newest one. The religious textif dealt with from a linguistic perspective will be associated with communicative frameworks which are oriented by direct and indirect features and characteristics to an implicit or explicit addressee. This speech has semantic issues and pragmatics’dimensions that appear in audio investigations with multiple purposes. .
مقال
Keywords: المقولات ؛ الوظيفية ؛ الدلالية؛ الفاعل؛ البؤرة; Quotation; Functionalism ; Semantics; the subject; The focus